Promoting Survivor Safety in Immigrant Communities: Online Simulation Training for Korean American Faith Leaders - Choi, Y. Joon (Journal of interpersonal violence, 2023)
This study examined the efficacy of a short virtual case simulation for Korean American (KA) faith leaders, “Religious Leaders for Healthy Families.” The goal of the program is to increase knowledge about intimate partner violence (IPV) and healthy intimate partner relationships, enhance self-efficacy in IPV prevention and intervention, strengthen attitudes that support their roles on IPV prevention and intervention, increase positive outcome expectations of their actions, and increase behavioral intentions and behaviors on IPV prevention and intervention. KA faith leaders from two large metropolitan areas with a high concentration of KA immigrants were invited to participate in the study (N=102). Participants completed three online assessments: baseline, a 3-month, and a 6-month follow-up. After the baseline assessment, participants were randomized to either intervention (n = 53) or control (n = 49). The intervention consisted of four online simulation modules, each taking approximately 15–20 min to complete. At the 6-month follow-up, faith leaders in the intervention group significantly increased their knowledge and self-efficacy in IPV prevention and intervention compared to the control group. Mean scores for attitudes against IPV and prevention behaviors increased from baseline to the 6-month follow-up for the intervention group more than the control group, but the differences were not statistically significant. “Religious Leaders for Healthy Families” has the potential to reduce disparities in accessing resources and services for immigrant survivors of IPV. With its ease of use, this short, free online intervention has a high potential for uptake among faith leaders. Results are promising, but the COVID-19 pandemic negatively affected the study, with participants having scarce opportunities to practice the skills learned from the intervention. A larger follow-up study that combines “Religious Leaders for Healthy Families” with a community-wide intervention that targets all community members is warranted to reach more faith leaders and community members.